The Diplomacy of the Great Powers Towards Albania in the Context of the â€œAdriatic Questionâ€ - Luku, Esilda (Mediterranean Journal of Social Sciences, 2012)
This paper aims to analyze the factors that influenced the diplomacy of the Great Powers towards the Albanianquestion at the Paris Peace Conference (1919-1920). Treated not as a special case, its fate was integrated with the solution ofthe â€œAdriatic questionâ€, meaning the rivalry between Italy and Yugoslavia to exert influence over the Eastern Adriatic. Thus, theGreat Powers didnâ€™t respect the sovereignty and the territorial integrity of Albania aimed at meeting its neighborsâ€™ intentions,such as: the Italian sovereignty over Valona and the hinterland, and the mandate for a small autonomous state in the CentralAlbania; the Yugoslavian pretensions to the North part of Albania and the Greek claims for the so-called â€œNorthern Epirusâ€. Forthat reason, the Great Powers reached political compromises and signed the memoranda of 9th December, 1919, and theagreement of 13th January, 1920, that foresaw the fragmentation of Albania between three neighboring countries. Fortunately, itwas the decisive role of the American President, W. Wilson that separated the Albanian question from the Adriatic one and let itopen to be discussed to other international forums.